Riedel’s Thyroiditis: Pitfalls in Diagnosis and Subsequent Complications - R. Pandev; M. Khan; V. Ratheesh (Case Reports in Endocrinology)
Riedel’s thyroiditis is a rare disease of chronic inflammation with fibrotic infiltration of the thyroid gland and its surrounding vital structures. Due to its low incidence, there are often delays in diagnosis as it is commonly mistaken for other thyroid diseases. We report the case of a 34-year-old female patient who presented with a firm, enlarged mass in the neck, compression symptoms, and hypothyroidism. Lab tests showed elevated A-TG (thyroglobulin antibodies) and A-TPO (thyroid peroxidase antibodies) levels. Based on the disease presentation and supporting lab findings, the patient was misdiagnosed with Hashimoto’s thyroiditis and treated accordingly. Yet the patient’s symptoms grew progressively worse. She was discovered to have severe tracheal compression and bilateral RLN (recurrent laryngeal nerve) palsy. Tracheotomy became a necessary surgical intervention after the development of respiratory failure, but this procedure was complicated by the development of an intraoperative pneumothorax. After an open biopsy, histology revealed Riedel’s thyroiditis. A new treatment was introduced, with which the patient’s condition improved. However, she continued to suffer from the open tracheocutaneous fistula left by the tracheostomy, which adversely affected her everyday life. A follow-up operation was performed to close the fistula. In this case report, we discuss the consequences of misdiagnosing the patient and delaying the appropriate treatment for her disease.